Exploration of Indigenous Tamang Identity and Values in Yambunera - Chalise, Keshav Raj (Janapriya Journal of Interdisciplinary Studies, 2022)
Examining the identity politics of Tamang people – about what and how Tamang identity is made to mean and the effects of their articulation- through literary writing, especially in Yambunera, is the central concern of this research work. As writing is the best way to express real-life experience and the mode of cultural practice, this study examines how Tamang indigenous identity is properly reflected in Yambunera and how particular aspects of Tamang life style and behaviours can be meaningful in searching for their indigenous identity. ‘Yambu’, as a symbol, Tamang people are at the marginal state, always away from Yambu, the centre of politics, power, rights and central culture. They are obliged to accept the position silently or have to speak for their rights and identity. In both conditions, they live with their identity. This identity is the heritage and the storehouse of their understanding and anticipation of system of life. It includes and represents the community attached to their geo-cultural identity. The language Tamang people speak, the profession they adopt from their tradition, the cultural practice they anticipate, and the traditional outfits they wear really parade their real impressions of indigenous identity. This research explicates different modes of indigenous identity of Tamang people reflected in Yambunera on the basis of the theory of Indigenous Studies.